Epigenetic silencing of neurofilament genes promotes an aggressive phenotype in breast cancer - Calmon, Marilia Freitas; Jeschke, Jana; Zhang, Wei; Dhir, Mashaal; Siebenkäs, Cornelia; Herrera, Alexander; Tsai, Hsing-Chen; O’Hagan, Heather M.; Pappou, Emmanouil P.; Hooker, Craig M.; Fu, Tao; Schuebel, Kornel E.; et al. (Taylor & Francis, 2015)
Neurofilament heavy polypeptide (NEFH) has recently been identified as a candidate DNA hypermethylated gene within the functional breast cancer hypermethylome. NEFH exists in a complex with neurofilament medium polypeptide (NEFM) and neurofilament light polypeptide (NEFL) to form neurofilaments, which are structural components of the cytoskeleton in mature neurons. Recent studies reported the deregulation of these proteins in several malignancies, suggesting that neurofilaments may have a role in other cell types as well. Using a comprehensive approach, we studied the epigenetic inactivation of neurofilament genes in breast cancer and the functional significance of this event. We report that DNA methylation-associated silencing of NEFH, NEFL, and NEFM in breast cancer is frequent, cancer-specific, and correlates with clinical features of disease progression. DNA methylation-mediated inactivation of these genes occurs also in multiple other cancer histologies including pancreas, gastric, and colon. Restoration of NEFH function, the major subunit of the neurofilament complex, reduces proliferation and growth of breast cancer cells and arrests them in Go/G1 phase of the cell cycle along with a reduction in migration and invasion. These findings suggest that DNA methylation-mediated silencing of the neurofilament genes NEFH, NEFM, and NEFL are frequent events that may contribute to the progression of breast cancer and possibly other malignancies.
Keywords: Breast cancer; DNA methylation; NEFH; NEFL; NEFM; TCGA